Pengaruh Geometri Terhadap Performa Latent Heat Thermal Energy Storage (Lh-Tes) Jenis Anulus Dengan Lilin Parafin Sebagai Phase Change Material (PCM) - Chaidier Ismail Halis (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2020)
A simulation-based study was conducted to model the transient phenomenon of heat transfer on Latent Heat Thermal Energy Storage (LH-TES) annular type with Phase Change Material (PCM) on the inner side and uses water as Heat Transfer Fluid (HTF) circulating on the outer side. A computational fluid dynamics model is developed to observe that phenomenon and validated with experimental data. The model is used to analyze the effect of geometry on improving LH-TES performances. An enthalpy-porosity formulation is adopted to model the melting process of the PCM. Geometry variation was done by enlarging the diameter of the pipe used both inside and outside. A value obtained by comparing the enthalpy value of fully melted PCM with the time take to reach that phase is used to quantify the performance of LH-TES. The result shows that the diameter enlargement of the inner pipe does increase LH-TES heat transfer performance up to 7.74%, while diameter enlargement of the outer pipe does decrease LH-TES heat transfer performance up to 1.04%. Keywords: Heat Transfer, Computational Fluid Dynamics, LH-TES